Cannibalism, growth performance, and body composition of giant trahira juveniles under different photoperiods - Ramos, Shayenne Elizianne; Carvalho, Aline Ferreira Souza de; Castro, Tássia Flávia Dias; Vasconcelos, Ana Carina Nogueira; Veras, Galileu Crovatto; Mourão Júnior, Carlos Alberto; Murgas, Luis David Solis (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to determine the effect of photoperiod on the cannibalism, growth, and body composition of giant trahira (Hoplias intermedius) juveniles. A completely randomized design was employed, with four photoperiods – 0L:24D, 6L:18D, 12L:12D, and 18L:6D, hours of light (L): dark (D) – and four replicates, for a period of 90 days. The analyzed parameters were: cannibalism, growth in weight and length, food consumption, feed conversion, protein efficiency rate, muscle growth, and body composition (moisture, lipid, ash, and crude protein). Fish from the 12L:12D photoperiod showed the highest survival rate and no cannibalism, as well as a great uniformity for length and mass values at the end of the experiment. The best photoperiod for giant trahira juveniles is 12L:12D, as these fish showed growth uniformity and no cannibalism, while fish from the 6L:18D and 18L:6D groups had a greater diameter of white muscle fibers and a higher frequency of greater diameter fibers. Giant trahira showed the lowest value for lipids at 6L:18D and the highest value at 12L:12D. Photoperiod affects survival and cannibalism; regarding body composition, only lipids are influenced by photoperiod.